HIV in Madagascar: Cause for Alarm - Betombo , Snyders Jessico; Raharivelo, Mitsou; Walsh, Andrew (Anthropologica, 2025)
In line with the work of a growing number of concerned researchers, this brief article draws attention to certain features of Madagascar’s looming HIV crisis. Reporting on the findings of a survey conducted with patients of a clinic that has recently hosted a large-scale screening program, we focus especially on what is and is not known about the transmission, effects, and treatment of HIV, and on why an elevated infection rate among the clientele of this clinic (many of whom are involved in artisanal mining) should be of special concern. Anticipating the return of long absent awareness-raising campaigns concerning HIV in Madagascar, we close with some cautious recommendations on what they might cover and how they might be carried out.